2020
DOI: 10.1007/s41464-020-00083-1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical (Dis‑)Integration and Firm Performance: A Management Paradigm Revisited

Abstract: Vertical disintegration in manufacturing industries has been an increasing trend since the 1990s in many countries. According to a prevailing management paradigm of focusing on core competencies, firms should have vertically disintegrated (i.e. outsourced non-core competencies) to achieve cost savings, enhance competitiveness and improve firm performance. In line with this management paradigm, most empirical studies therefore hypothesized a negative linear relationship between the degree of vertical integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 85 publications
1
12
0
Order By: Relevance
“…As we know, automobile manufacturers have shifted from vertical integration towards smaller and leaner operations (HUallacháin and Wasserman 1999;Kaiser and Obermaier 2020). Firms have downsized and started focusing on core things to increase their competency by leveraging their suppliers' capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, automobile manufacturers have shifted from vertical integration towards smaller and leaner operations (HUallacháin and Wasserman 1999;Kaiser and Obermaier 2020). Firms have downsized and started focusing on core things to increase their competency by leveraging their suppliers' capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…The present research work targeted the 2009–2021 period, because vertical integration has regained momentum in the manufacturing industry especially after the 2008 global financial crisis (Kaiser and Obermaier 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the value-added to sales approach (VAS), vertical integration can be calculated by diving value-added by sales. Other common approaches are the inventory to sales ratio and the income to sales ratio (Adelman 1955 ; Kaiser and Obermaier 2020 ). In comparing different measurement methods, Adelman ( 1955 ) observed that a simple way to determine the degree of backward vertical integration is to calculate, with respect to a given product, what percentage of inputs used by the firm is produced in-house.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, two distinct measures of vertical integration can be identified in the literature. These include measures determined from financial statements and the use of multidimensional constructs such as computation of indices based on available data (Kaiser and Obermaier, 2020).…”
Section: Vertical Integration and Its Measurementmentioning
confidence: 99%